“Formed with Curious Skill”: Blessington’s negotiation of the “poetess” in Flowers of Loveliness - Hawkins, Ann (Romanticism on the Net, 2003)
AbstractThis essay demonstrates how Marguerite, Countess of Blessington, relied upon but also diverged from poetess poetics as a way of forging her own poetic voice without sacrificing the economic success enjoyed by anyone willing to write poetry in the style and manner of the annuals. As a close-reading of both content and context of Blessington’s satiric poem “The Stock in Trade of the Modern Poetess” reveals, Blessington capitalizes on her Byronic disdain for the annuals, thus simultaneously spurning poetess poetry and making a bid for financial success, the success typically enjoyed by writers willing to truck in poetess “stock.” In order to achieve both financial success and poetic merit, Blessington plays to the crowd who expects beautiful images of the nation in poetess poetry, but not by using the same "stock" as does poetess poetry: instead of setting up national heroines to be worshipped, Blessington recasts typical symbols used by the poetess for romantic and domestic relationships as ties that bind one person to another in the nation. Blessington’s oeuvre illustrates one dramatic instance of participation in the poetess tradition, showing us that women writers didn’t simply succumb to poetess conventions but rather manipulated the “stock in trade” of the poetess in order to achieve literary without sacrificing financial success.